A Novel Approach to Search for Identity by Descent in Small Samples of Patients and Controls from the Same Mendelian Breeding Unit: A Pilot Study on Myopia - Heath, Simon; Robledo, Renato; Beggs, William; Feola, Gaetano; Parodo, Carlo; Rinaldi, Antoniettina; Contu, Licinio; Dana, Debra; Stambolian, Dwight; Siniscalco, Marcello (Human heredity, 2001)
Autosomal dominant high myopia, a genetic disorder already mapped to region 18p11.31, is common in Carloforte (Sardinia, Italy), an isolated village of 8,000 inhabitants descending from a founder group of 300 in the early 1700s. Fifteen myopic propositi and 36 normal controls were selected for not having ancestors in common at least up to the grandparental generation, although still descendants of the original founders. All subjects were genotyped for 14 markers located on autosome 18 at a resolution of about 10 cM. Allelic distributions were found to be similar at all tested loci in propositi and controls, except for the candidate marker D18S63 known to segregate in close linkage association with high myopia. In particular, the frequency of allele 85 among the propositi was almost double that of the controls (Fisher’s exact test, p = 0.037). The association is more striking when the frequency of the genotype 85/85 in the two groups is compared (Fisher’s exact test, p = 0.005). This conclusion was further evaluated through a bootstrap analysis by computing the overall probability of the observed data under the null hypothesis (i. e. no difference between the two groups in frequency distributions for the chromosome 18 markers). Again, marker D18S63 was found to have a sample probability lower than 0.004, which is significant at the 0.05 level after correcting for simultaneous testing of multiple loci. The study demonstrates the efficiency of our novel strategy to detect identity by descent (IBD) in small numbers of patients and controls when they are both part of well-defined Mendelian breeding units (MBUs). The iterative application of our strategy in separate MBUs is expected to become the method of choice to evaluate the ever-growing number of reported associations between candidate genes and multifactorial traits and diseases.